REKSA DANA PENDAPATAN TETAP DI INDONESIA: ANALISISPEMILIHAN SEKURITAS DAN ANTISIPASI WAKTU - Herlyna Oktavia, (2013)
This study is performed to examine the effect of Bond Selection and Market Timing toward Fixed Income Mutual Funds Performance period 2011. The population of this research is 118 fixed income mutual funds listed on the Badan Pengawas Pasar Modal dan Lembaga Keuangan period of 2011. The sampling technique used here is purposive sampling, and obtained a sample of 59 fixed-income mutual funds. The data required to support the analysis and hypothesis is secondary data obtained from the Badan Pengawas Pasar Modal dan Lembaga Keuangan, Bank Indonesia, and Invofesta. The results of this study indicate that simultaneous variables of bond selection and market timing having a significant effect on the fixed income mutual funds performance. While the results of research conducted partially indicates that the variable of Bond Selection does not affect on the fixed income mutual funds performance. And variable market timing have significantly negative effect on the fixed income mutual funds performance.